IMPROVING OF BASKETBALL GAME LEARNING OUTCOMES WITH STUDENTS’ LEARNING GROUP INVESTIGATION - Naheria Naheria; Baso Amiruddin; Muh. Ramli Buhari (Acitya: Journal of Teaching and Education, 2021)
This study aims to improve the learning outcomes of passing and dribbling basketball in Samarinda State Vocational School 17 students in 2019/2020 academic year using a cooperative group type investigation model. This research was conducted in two cycle, which consists of four stages namely planning, implementing, observing and reflecting actions for each cycle. The research subjects were students of pharmacy class XI-1 of SMK Negeri 17 Samarinda in the 2019/2020 school year, totaling 32 students, 5 students and 27 students. Data sources of this research are students and teachers. Data collection techniques used in this study were to test skills, knowledge and also observation of student behavior as an assessment of aspects of attitude. Data analysis uses descriptive analysis techniques that are based on qualitative and quantitative analysis. The results of the study show that using a cooperative group type cooperative model can improve learning outcomes of basketball passing and dribbling in students from pre-cycle to cycle one from cycle one to cycle two. From the analysis of data obtained from the results of cycle one an increase in the results of learning to pass and dribble basketball is complete that is 43.75% or 14 students who complete. While the second cycle increases the learning outcomes of basic techniques of passing and dribbling basketball by 100% or 32 students who are complete. Based on the results of the study it can be concluded that using the cooperative learning model type of investigation is appropriate in basketball learning especially the basic techniques of passing and dribbling.